Islamic Education Based on Sufistic Counseling: Integrating Psychosufistic (Sufism) and Islamic Spiritual Counseling Approaches to Develop Islamic Character - Prio Utomo; Tiara Agustine; Augusto Da Costa; Nor Junainah Mohd Isa (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: Islamic Education Based on Sufistic Counseling: Integrating Psychosufistic (Sufism) and Islamic Spiritual Counseling Approaches to Develop Islamic CharacterObjective: This study aims to integrate the psychosufistic (Sufism) approach with Islamic spiritual counseling in shaping Islamic character as the foundation for a model approach. Methods: This research employs a Systematic Literature Review (SLR). Data sources were obtained from scholarly journals indexed in Scopus, Web of Science, and Google Scholar. Data analysis was conducted using content analysis techniques (applying inclusion and exclusion criteria). Results: Integrating the psychosufistic (Sufism) approach and Islamic spiritual counseling in shaping Islamic character emphasizes the individual's efforts in self-purification (tazkiyyatunnafs) and devotion to Allah SWT. Conclusion: Integrating the psychosufistic approach with Islamic spiritual counseling can serve as an effective strategy for shaping Islamic character. Contribution: This study contributes to Islamic education, by integrating the psychosufistic approach with Islamic spiritual counseling.INDONESIAN: Pendidikan Islam Berbasis Konseling Sufistik: Mengintegrasikan Pendekatan Psikosufistik (Tasawuf) dan Konseling Spiritual Islam untuk Membentuk Karakter IslamiTujuan: Penelitian ini bertujuan untuk mengintegrasikan pendekatan psikosufistik (tasawuf) dengan konseling spiritual islam dalam membentuk karakter islami sebagai basis model pendekatan. Metode: Jenis penelitian ini menggunakan Systematic Literature Review (SLR). Sumber data diperoleh dari jurnal ilmiah yang terindeks Scopus, Web of Science, dan Google Scholar. Analisis data menggunakan teknik analisis konten (kriteria inklusi dan eksklusi). Hasil: Integrasi pendekatan psikosufistik (tasawuf) dan konseling spiritual islam dalam membentuk karakter islami menekankan pada upaya individu untuk penyucian diri (tazkiyyatunnafs) dan pengabdian kepada Allah SWT. Kesimpulan: Intergrasi pendekatan psychosufistic dengan konseling spiritual islam dapat menjadi strategi pendekatan dalam membentuk karakter Islami. Konstribusi: Penelitian berkontribusi sebagai referansil ilmu pengetahuan di bidang pendidikan islam berbasis integrasi pendekatan psychosufistic dengan konseling spiritual islam